Dorotea gen. nov., a new bathyal genus (Amphipoda, Eusiridae) from the Solomon Sea (Papua New Guinea) - Corbari, Laure; Frutos, Inmaculada; Sorbe, Jean Claude (Zootaxa, 2019)
A new species ascribed to a new genus of Eusiridae, Dorotea papuana gen. nov., sp. nov. is described from bathyal bottoms of the Solomon Sea (Papua New Guinea). Closely related to the genus Cleonardo, this new genus can be distinguished from most other known eusirid genera by the presence of a telson distally cleft and distinctly bilobate, of a distal spiniform process on uropod 1 peduncle and of a simple, stout and medium length dactylus on pereopods 5–7. The combination of all these characters can be considered relevant for the affiliation of this species to a new genus within Eusiridae. Due to its very close morphological affinity to Dorotea gen. nov., the bathyal sub-Antarctic species Eusiroides aberrantis Bellan-Santini & Ledoyer, 1987 cannot be maintained in the family Pontogeneiidae and it should be transferred to the family Eusiridae.